Partikeldetektion in mikrofluidischen Systemen - Kettlitz, Siegfried (KIT Scientific Publishing, 2015)
Analysis of microparticles is an important tool in medicine, biology and chemistry. In order to address future application areas, new systems will be produced by printing technology. In this work new microfluidic particle detection systems which employ planar optics are developed and analyzed. Because the characteristic of these new systems differs greatly from established particle detection systems the signals and statistics are analyzed in depth.